The implication of aberrant NRF2 activation in management of female cancers - Kgatle, Mankgopo; Mbambara, Saidon; Fadebi, Olalekan; Kabunda, Joseph; Kaoma, Chimbabantu; Dlangalala, Thobeka; Nxele, Siphesihle; Modipane, Ndimo; Serite, Thato; Mokoala, Kgomotso; Mashamba-Thompson, Tivani; Sathekge, Mike (Frontiers in Oncology, 2025)
The overactivation of NRF2 (Nuclear factor erythroid 2-related factor 2) in female malignancies is an emerging field of study with significant implications for treatment efficacy. NRF2 plays a pivotal role in managing inflammation-induced oxidative stress, which is crucial components of the tumor microenvironment. Acting as a transcription factor and basic leucine zipper protein, it regulates the expression of various antioxidant genes that safeguard cells from oxidative stress and damage. While NRF2 activation is beneficial for the survival of normal cells, its overactivation in cancer cells can enhance tumor cell survival, proliferation, and resistance to treatments. Importantly, NRF2 has a dual context-dependent role, functioning as a tumor suppressor when transiently activated in normal cells to prevent carcinogenesis, but as an oncogene when persistently activated in established tumors. Understanding NRF2’s transcriptional alterations and developing targeted therapies could improve cancer management, prognosis and treatment outcomes, making it a promising target for precision oncology. This review aims to provide a comprehensive overview of NRF2 activation in female malignancies, including cervical, endometrial, ovarian, vaginal, vulvar and, breast cancers, and its association with chemoresistance, highlighting challenges and opportunities for developing more effective cancer treatments.